STUDI KOMPARASI MODEL PEMBELAJARAN SEJARAH DI SMA TARUNA NUSANTARA DAN SMA NEGERI 4 MAGELANG - Muhammad Fendi Aditya (Universitas Negeri Yogyakarta, 2016)
This study aims to determine : (1) Knowing the policy of principals at Taruna Nusantara High School and Senior High School 4 Magelang to subjects of History, (2) Knowing the curriculum policy regarding the portion of the placement of the subjects of History, (3) how teachers deliver material and learning models History in high school of Taruna Nusantara High School and Senior High School 4 Magelang, and (4) how student opinion in History teachers the material. The results of the study at both schools led to the fact that Taruna Nusantara High School is promoting subjects as the history of important subjects, subjects using history as a spearhead in the successful implementation of special curriculum-based defend the country. Especially in the formation of character and cultivation of the spirit of nationalism, the students really enjoyed how the delivery of interesting material presented by the teacher of history at this school, teachers use a good individual approach so as to maximize the potential of students. In Senior High School 4 Magelang put the subjects of history into something very interesting because of factors that creative and innovative teachers of these subjects were used as a means of knowledge transfer that is very positive. Keywords: Comparative Studies, History Learning Model